Understanding process intensification in cyclic distillation systems - Maleta, Vladimir; Kiss, Anton; Taran, Vitaly; Maleta, Bogdan (My University, 2011)
The most effective separation possible in distillation columns takes place in the hydrodynamic regime where there is perfect displacement of the liquid and vapor streams. This can be achieved in distillation equipment with separate phase movement (SPM). Such an innovative route for process intensification in distillation is called cyclic distillation. The required process conditions are the lack of liquid outflow from the tray during vapor admission and the lack of liquid mixing in adjacent trays upon outflow of liquid. Remarkably, the throughput of such a column that operates in a controlled cycle mode is two or more times higher than the throughput reachable with conventional operation, at equivalent separation performance. In this study, a theoretical stage model with perfect displacement is proposed and the theory of the process working lines is developed. An adequate mass transfer model is also described along with the mode of calculation of tray columns operating in the cyclic operation mode. Sensitivity analysis was used to determine the effect of the key model parameters. The theoretical developments were implemented at industrial scale and subsequent testing showed an increase in the separation efficiency of 2-3 times as compared to the standard process.
Keywords: циклічні дистиляції; контрольована періодична операція; модель масопередачі; досконалий зміщення; циклические дистилляции; контролируемая периодическая операция; модель массопередачи; совершенный смещения; cyclic distillation; controlled periodic operation; mass transfer model; perfect displacement; кафедра машин і апаратів харчових та фармацевтичних виробництв